Perancangan Ulang Gereja Kristen Indonesia Pengadilan Bogor Dengan Pendekatan Religius Simbolik Sakral Calvinisme - Lidya Emanuella Seumahu, Marscha; Nur Arief Hapsoro, Agustinus; Aulia Widyaevan, Dea (eProceedings of Art & Design, 2024)
The redesign of the Indonesian Christian Church (GKI) Pengadilan Bogor intends to design the main worship space of the church that can facilitate as a whole, especially the main worship space used for worship activities every week, then this design also includes rooms used for church community activities in it, as well as solving technical problems such as lighting and sound that affect the sacredness in the church. Because of the existing problems, the redesign of GKI Pengadilan Bogor is needed. The approach used in this redesign is the Calvinism sacred symbolic religious approach to create a sacred worship space and in accordance with the teaching of Christianity, especially the flow based on Calvinism, but also in its application will be considered the function of supporting spaces for church community activities in order to be well facilitated. These spaces include multipurpose rooms, felllowship rooms, Sunday school rooms and small worship rooms. The technical problems of the church will be considered based on the function and use of the spaces in this church. Keywords: church, religious approach, sacred, community activities